Karakteristik Fisikokimia dan Kadar Betakaroten Susu Sapi dengan Penambahan Puree Labu Kuning - Arif Ismanto; Qonitha Aqila Shofi; Muh. Ichsan Haris; Khoiru Indana (PT. PENERBIT TIGA MUTIARA, 2026)
Cow's milk is a nutritious food that can be developed into a functional food through the addition of natural ingredients rich in β-carotene, such as pumpkin puree. This study aimed to analyze the effect of pumpkin puree addition on the physicochemical characteristics and β-carotene content of cow's milk and to determine the optimum formulation. The study employed four treatments, namely P0 (0%), P1 (5%), P2 (10%), and P3 (15%) pumpkin puree addition. The observed parameters included pH value, color (L*, a*, and b*), fat content, and β-carotene content, which were analyzed using analysis of variance (ANOVA) at a 5% significance level. The results showed that the pH remained stable within the range of 6.77-6.79, lightness (L*) decreased, while redness (a*), yellowness (b*), and β-carotene content increased. The highest β-carotene content was obtained in treatment P2 at 2,805.0 µg/100 mL, whereas the fat content ranged from 24.93% to 34.04%. The study concludes that the addition of pumpkin puree significantly affects the physicochemical characteristics and increases the β-carotene content of cow's milk, with the optimum formulation achieved by adding 10% pumpkin puree. The novelty of this study lies in determining the optimum pumpkin puree formulation based on an integrated evaluation of physicochemical characteristics and β-carotene content in pasteurized cow's milk.